Early acute kidney injury in sepsis and septic shock - Hoang, Trong Hanh; Hoang, Dong; Phan, Van Minh Quan; Nguyen, Vinh Phu; Tran, Thuy Quynh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Background: Acute kidney injury is one of the severe conditions in hospitalized patients. Acute kidney injury can develop early from admission, usually within the first 24 hours of ICU admission. In Vietnam, there have been limited studies monitoring the progression of acute kidney injury in the early stages. This study aims to investigate the incidence, severity, clinical, laboratory characteristics, and progression of acute kidney injury in patients with sepsis and septic shock within the first 48 hours. Methods: This study is a cross-sectional descriptive analysis of 101 patients who are 15 or older and have been diagnosed with severe infection and septic shock. These patients were treated in the Intensive Care Unit of Hue Central Hospital. The patient had treatment in accordance with a standardized protocol while being closely observed. Samples were collected for diagnostic testing, and the patient’s urine output and blood creatinine levels were diligently checked. Results: The prevalence of acute renal injury (AKI) was 60.40%, with stage 1 accounting for 50.82% of cases, stage 2 accounting for 22.95%, and stage 3 accounting for 26.23%. The cohort of individuals diagnosed with AKI exhibited an advanced age, with a mean age of 60.72 ± 17.41 years, and predominantly consisted of male subjects. Patients diagnosed with acute kidney injury showed a statistically significant decrease in urine output and an increased incidence of shock (p < 0.05). Additionally, these patients demonstrated lower levels of Hct, blood pH, and bicarbonate while exhibiting higher levels of blood urea, blood creatinine, AST, ALT, total bilirubin, PCT, and blood lactate (p < 0.05) compared to individuals without AKI. Patients with AKI had significantly elevated SOFA and APACHE II scores compared to individuals without AKI, as indicated by statistical analysis (p < 0.05). Upon admission, a significant proportion of patients, precisely 81.97%, experienced the development of AKI. Furthermore, a observation was made about the prompt recovery of these patients within the initial 24 and 48 hours following admission. Conclusion: The prevalence of AKI was accounted for 60.40%. Among the cases of AKI, stage 1 accounted for 50.82%, while stage 2 and stage 3 accounted for 22.95% and 26.23%, respectively. There were observed variations in urine output and rates of shock among individuals diagnosed with AKI. Additionally, SOFA and APACHE II scores were elevated. The percentage of AKI was 81.97% of patients upon their initial hospital admission, with a significant proportion seeing early recovery within the first 24 to 48 hours.